2016
DOI: 10.3892/ijo.2016.3464
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Notch3 inhibits the stem-like property and is associated with ALDH1A1 and CD44 via autophagy in non-small lung cancer

Abstract: Acquired resistance to standard chemotherapy causes treatment failure in patients with local advanced and advanced non-small lung cancer (NSCLC). Cancer stem cells (CSCs) are a small subpopulation within cancer that is thought to be resistant to conventional chemotherapy. The Notch pathway is one of the most intensively studied for putative therapeutic targets of CSCs in solid tumors. In our study, suppression of Notch3 decreased colony and sphere formation of stem-like property in lung cancer cells. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…The process of autophagy involves complex autophagy regulating pathways. RGD, CD44, p38 MAPK, and Erk1/2 are among the familiar signaling pathways thought to be involved in cell autophagy [21, 22]. Survival factors, growth factors, and cytokines can activate upstream pathways like MAPK or Erk1/2 that could, in turn, regulate the mTOR pathway [23].…”
Section: Introductionmentioning
confidence: 99%
“…The process of autophagy involves complex autophagy regulating pathways. RGD, CD44, p38 MAPK, and Erk1/2 are among the familiar signaling pathways thought to be involved in cell autophagy [21, 22]. Survival factors, growth factors, and cytokines can activate upstream pathways like MAPK or Erk1/2 that could, in turn, regulate the mTOR pathway [23].…”
Section: Introductionmentioning
confidence: 99%
“…As a candidate for a regulator of a stem-like phenotype in NRF2-activated NSCLC cells, we selected NOTCH3 among the NRF2-activated NSCLC-specific NRF2 downstream effectors ( Figure 1f and Extended Figure 2) based on a previous report showing that NOTCH3 contributes to a stem-like phenotype of NSCLC (Zheng et al, 2013;Ma et al, 2016).…”
Section: Notch3 Is a Unique Downstream Effector Of Nrf2 In Nrf2-activmentioning
confidence: 99%
“…It was significantly associated with higher tumor recurrence and metastatic involvement in the subset of patients that was analyzed [60]. On the other hand, two other studies found that Notch-2 that suppresses apoptosis, can promote the differentiation of Clublike cells, which are the resident stem cell-like cells in lung tissues and was predictive of longer OS [53,61] Studies have shown that Notch-3 is tumor-promoting and indicative of shorter DFS and OS, higher tumor stage, lymph node metastasis and poorer tumor differentiation status [52,53,62,63,64]. It has been implicated in resistance acquisition to cisplatin and poor response to platinum-based chemotherapy.…”
Section: Clinical Evidencementioning
confidence: 99%